Revisiting the usefulness of the short acute octreotide test to predict treatment outcomes in acromegaly - Marques-Pamies, Montserrat; Gil, Joan; Valassi, Elena; Hernández, Marta; Biagetti, Betina; Giménez-Palop, Olga; Martínez, Silvia; Carrato, Cristina; Pons, Laura; Villar-Taibo, Rocío; Araujo-Castro, Marta; Blanco, Concepción; et al. (Frontiers in Endocrinology, 2023)
Patients with E-cadherin positive tumors showed a lower GH2h than those negative [0.9 (0.3-2.1) vs 3.3 (1.5-12.1) ng/mL; p<0.01] and patients with positive E-cadherin presented a higher score of SSTR2 (7.5±4.2 vs 3.3±2.1; p=0.01). CONCLUSIONS: The sAOT is a good predictor tool for assessing response to SRLs and correlates with tumor E-cadherin and SSTR2 expression. Thus, it can be useful in clinical practice for therapeutic decision-making in acromegalic patients.Prediction tools to assess response to medical treatment in acromegaly are necessary. The short version of the acute octreotide test is an easy, inexpensive, and sufficiently informative test that can help the clinician to identify responsiveness to SRLs in acromegaly.1.